COMPARATIVE ANALYSIS ON SERVICE QUALITY OF MOBILE SHOPPING APPLICATION (CASE STUDY: SHOPEE AND TOKOPEDIA) - Ramadhani, Desita Wahyu; Suharto, Yulianto (Journal of Business and Management, 2018)
Abstract.These days, as the effect of the technology advancement, internet keep growing rapidly. Internet has a role to help people in almost everything. This phenomenon created some new opportunities for people in conducting their business. The selling and buying activities can be done everywhere and without meeting each other, they can utilize their mobile. There are two big companies that successfully dominate the market in Indonesia, that are Shopee and Tokopedia. These two companies as the most used mobile shopping application in Indonesia have to maintain their quality of service in running their business. The purpose of this research is to compare the service quality of Shopee and Tokopedia mobile shopping application and also to analyze the differences using MS-QUAL dimension that are Contact, Responsiveness, Fulfillment, Privacy and Efficiency. The data collected is 200 respondents from each Shopee and Tokopedia mobile shopping application users. The analysis method used in this study is Mann Whitney to analyze the differences of two independent samples. Results indicate that there is no significant difference on Contact, Responsiveness, Fulfillment and Efficiency dimension between Shopee and Tokopedia. Whereas, there is significant difference on Privacy dimension between Shopee and Tokopedia. This study arrives to a recommendation that Tokopedia should improves privacy dimension on the mobile shopping application in order to compete with Shopee as the most used mobile shopping application in Indonesia.Keywords: Mann Whitney, Mobile Service Quality, Mobile Shopping Application, Shopee, TokopediaÂ Â